1990
DOI: 10.1007/bf00000032
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced shape transformation of carrier erythrocytes

Abstract: Erythrocytes have been proposed as cellular carriers for enzymes and drugs for protected delivery, slow release, or targeting to specific organs. Several studies have established the heterogeneity of resealed carrier erythrocytes concerning various characteristics, including morphology. Carrier erythrocytes were prepared by hypo-osmotic dialysis and consecutive iso-osmotic resealing at different temperatures, and the morphology of these cells was studied by scanning electron microscopy. Different cell shapes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…3c). Earlier studies, in fact, demonstrated that cell membrane’s pores remain open for a longer time at lower temperature compared to higher temperature (23,24). …”
Section: Resultsmentioning
confidence: 99%
“…3c). Earlier studies, in fact, demonstrated that cell membrane’s pores remain open for a longer time at lower temperature compared to higher temperature (23,24). …”
Section: Resultsmentioning
confidence: 99%